Effect of H pylori infection and its eradication on hyperammo-nemia and hepatic encephalopathy in cirrhotic patients - Chen, Shu-Jie; Wang, Liang-Jing; Zhu, Qin; Cai, Jian-Ting; Chen, Tao; Si, Jian-Min (World journal of gastroenterology : WJG, 2008)
To investigate the relationship between H pylori infection, blood ammonia concentration and hepatic encephalopathy (HE), and the effect of H pylori eradication in cirrhotic patients. From July 2003 to January 2005, 457 cirrhotic patients in five regions of Zhejiang Province were enrolled. Patients were evaluated for demographics, number connection test, H pylori infection, liver impairment, blood ammonia concentration and HE. Patients with H pylori infection were given 1 wk therapy with omeprazole plus clarithromycin and tinidazole. (14)C urea breath test was performed and mental symptoms and blood ammonia level were reassessed after bacterium eradication. Overall H pylori infection rate was 60.6%, and HE occurred in 47.5% of cirrhotic patients. Subclinical HE (SHE) was detected in 55 of 117 cirrhotic patients. Blood ammonia concentration in H pylori negative (n = 180) and positive (n = 277) cirrhotic patients was 53.8 +/- 51.4 and 78.4 +/- 63.6 mumol/L, respectively (P < 0.01), which was significantly reduced to 53.5 +/- 37.7 mumol/L after bacterium eradication (n = 126) (P < 0.01). Blood ammonia was 97.5 +/- 81.0 mumol/L in H pylori-positive cirrhotic patients, and this did not significantly change in those with persistent infection after H pylori eradication (n = 11). HE was more frequently observed in patients with H pylori infection than in those without (58.5% vs 30.6%, P < 0.01). HE rate significantly dropped to 34.1% after H pylori eradiation (P < 0.01). H pylori prevalence significantly differed among cirrhotic patients with HE (74.4%), SHE (69.1%), and those without HE (53.2%) (P < 0.05). Blood ammonia level was significantly different among cirrhotic patients with HE (94.5 +/- 75.6 mumol/L), SHE (59.9 +/- 49.2 mumol/L), and without HE (47.3 +/- 33.5 mumol/L) (P < 0.05). Logistic regression analysis showed that blood ammonia concentration, Child-Pugh stage, upper gastrointestinal bleeding, electrolyte disturbance, and urea nitrogen were risk factors for HE. H pylori infection is an important factor for inducing high blood ammonia concentration and HE in cirrhotic patients. H pylori eradication may be helpful for treatment and prevention of HE.